A Production and operations management study on Dragon Textile Mills, Inc. - Bangalan, Darwin P. (College of Engineering, 2003)
This study was conducted in order to determine the existing Operation Management related problems in the Dragon Textile Mill, Inc. a yarn-manufacturing company, then solving them through the applications of OM theories and techniques. The current system was evaluated by the use of Stream Diagnostic Diagram. Alternatives were then generated then evaluated. The three problems identified were in-house generator and machines frequency of breakdown, bottleneck on the process, and insufficient forecasting technique currently used by the company. The problem of machine breakdown was approached by finding the best time to do preventive maintenance for each machine that will minimize total maintenance cost. Alternatives were doing it weekly, bimonthly or the status quo (At the end of every cycle). By cost analysis, it was found out that open-end and drawing machines should have their preventive maintenance bi-monthly, and monthly for blowing and drawing machines.Bottleneck on the process on the other hand was approached by determining the effective method of reducing idle time of each machine while increasing their capacity. Alternatives were trying to match capacity with the demand during peak season, matching the capacity (reducing) of the open-end machine since it has the highest effective capacity among all the other machines and the status quo. On the basis of cost therefore alternative 1 is more advisable to take than alternative 2. And since the company has already excess capacity, adding more machines would mean more surplus of yarns and therefore higher holding cost of inventory. Alternative 2 on the other hand would become more advisable to take if the company is expecting an increase in the demand of yarns for the following years. Therefore instead of selling machines and then buying new machines again when demand has increased, it would be more advisable to buy the machines now since it would be more costly if the company sells its machine at a lower cost, then buy new ones later at a higher cost . Lastly, for the insufficient forecasting technique, the group tested other techniques and used the tracking signal in order to determine the forecasting technique, which will result closest to the actual demand. It was found out that the best technique should be used is the multiplicative seasonal model in order to have values closest to the actual demand. For the general recommendation, the proponents advised the company to change their preventive maintenance scheduling for all the machines in order to minimize frequency of breakdowns while keeping total maintenance cost at the least. Should this be done then the proposal to the second problem will be valid. And lastly, the company could easily implement the new forecasting method because it is very easy to use and requires very little training and lecture. The expected benefit would be that there would be less of stock-outs for coarse count yarn and consequently less cost for inventory keeping, since the forecasted demand would be almost the same as the actual demand.